Nuclear Receptor-Coregulator Interaction Profiling Identifies TRIP3 as a Novel Peroxisome Proliferator-activated Receptor γ Cofactor - Arjen Koppen; René Houtman; Dirk Pijnenburg; Ellen H. Jeninga; Rob Ruijtenbeek; Eric Kalkhoven (2009)
Nuclear receptors (NRs) are major targets for drug discovery and have key roles in development and homeostasis as well as in many diseases such as obesity, diabetes, and cancer. NRs are ligand-dependent transcription factors that need to work in concert with so-called transcriptional coregulators, including corepressors and coactivators, to regulate transcription. Upon ligand binding, NRs undergo a conformational change, which alters their binding preference for coregulators. Short alpha-helical sequences in the coregulator proteins, LXXLL (in coactivators) or LXXXIXXXL (in corepressors), are essential for the NR-coregulator interactions. However, little is known on how specificity is dictated. To obtain a comprehensive overview of NR-coregulator interactions, we used a microarray approach based on interactions between NRs and peptides derived from known coregulators. Using the peroxisome proliferator-activated receptor gamma (PPARgamma) as a model NR, we were able to generate ligand-specific interaction profiles (agonist rosiglitazone versus antagonist GW9662 versus selective PPARgamma modulator telmisartan) and characterize NR mutants and isotypes (PPARalpha, -beta/delta, and -gamma). Importantly, based on the NR-coregulator interaction profile, we were able to identify TRIP3 as a novel regulator of PPARgamma-mediated adipocyte differentiation. These findings indicate that NR-coregulator interaction profiling may be a useful tool for drug development and biological discovery.